(untitled) (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
The transition from high school to college is an important phase that is often accompanied by academic, social, and emotional pressures. One of the psychological factors that plays a role in facing this challenge is self-confidence. This study aims to evaluate the effectiveness of positive affirmations in increasing the self-confidence of high school students preparing to continue their education. The study used a quasi-experimental approach with a one-group pretest-posttest design. Six grade XII students at a high school in Padang City were selected purposively and completed 12 sessions of positive affirmation training. The instrument used was a self-confidence scale based on aspects according to Lauster. The results of the Wilcoxon Signed-Rank test showed a significant increase in self-confidence scores after the intervention (p = 0.034). These results indicate that positive affirmations are effective in increasing students’ self-confidence and have implications for the development of psychological intervention programs in schools. Masa transisi dari SMA ke perguruan tinggi merupakan fase penting yang sering disertai tekanan akademik, sosial, dan emosional. Salah satu faktor psikologis yang berperan dalam menghadapi tantangan ini adalah kepercayaan diri. Penelitian ini bertujuan mengevaluasi efektivitas afirmasi positif dalam meningkatkan kepercayaan diri siswa SMA yang mempersiapkan diri melanjutkan pendidikan. Penelitian menggunakan pendekatan kuasi-eksperimental dengan desain one group pretest-posttest. Enam siswa kelas XII di salah satu SMA di Kota Padang dipilih secara purposive dan menyelesaikan pelatihan afirmasi positif sebanyak 12 sesi. Instrumen yang digunakan berupa skala kepercayaan diri berdasarkan aspek-aspek menurut Lauster. Hasil uji Wilcoxon Signed-Rank menunjukkan peningkatan signifikan pada skor kepercayaan diri setelah intervensi (p = 0,034). Hasil ini mengindikasikan bahwa afirmasi positif efektif dalam meningkatkan kepercayaan diri siswa dan memberi implikasi bagi pengembangan program intervensi psikologis di sekolah.